The Use of Computer-Based Interactive Games in Teaching Science Con-cepts for Struggling Learners: Basis for a Compilation of Recommended Games in Teaching - Sumandal, Allan H. (Future Science / FSH-PH Publications, 2022)
Games have been used and proven effective in motivating students. Playing interactive games can enhance learning (Lieberman, 2006). This study aimed to evaluate the effectiveness of computer-based interactive games in teaching students who are struggling to learning concepts in Physical Science. It also determined to identify the students’ attitudes towards the use of computer-based interactive games. This study utilized pre-test and post-test designs. Respondents for this study were Grade 11 struggling learners and were determined based on the learners’ general average grade during the first semester. The two experimental treatment groups were randomly assigned. One group was taught using computer-based interactive games as an intervention, while the other did not have any teaching intervention. Both groups had regular class instruction in Physical Science and were taught the same content and the same amount of time. The findings reveal that upon exposure to computer-based interactive games, struggling students’ performance in science concepts as described by their pre-test and post-test scores were statistically different with the performance of the struggling students using the lecture-discussion approach. The result implies that students enhanced by the computer-based interactive games approach performed at par with those exposed to traditional learning. Hence, the use of computer-based interactive games in teaching Physical Science concepts is recommended, in addition to regular class instruction. It is suggested that science teachers, especially senior high school teachers who teach Physical Science, should integrate and use computer-based interactive games since it promotes a better understanding of the lesson.